The impacts of visual Art Therapy for elderly with Neurocognitive disorder: a systematic review - Leonardo Brynne Ramos de Souza; Yasmin Cabral Gomes; Márcia Goretti Guimarães de Moraes (Dementia & Neuropsychologia, 2022)
ABSTRACT. Aging is characterized by a reduction in physical, cognitive, and emotional functions, allowing multiple losses in the quality of life of the elderly. As a clinical situation that has a common association with pathological aging, neurocognitive disorder, previously named dementia, has become epidemiologically more relevant over the years. Thus, art therapy has recently emerged as an alternative technique for approaching these individuals, with the aim of improving cognitive, emotional, and quality of life aspects. Objective: The objective of this study was to analyze the effects of the application of art therapy based on visual creative processes on cognitive, emotional, and quality of life aspects in elderly people with neurocognitive disorder. Methods: This was a systematic review, carried out using CAPES, PubMed, SciELO, Bireme, PEDro, LILACS, and Scorpus databases between December 2020 and April 2021. Controlled and uncontrolled clinical trials were included in English, Spanish, French, and Portuguese, published between 1970 and 2021, with a focus on modalities of visual art production. The articles included at the end of the selection process were evaluated methodologically by the PEDro Scale of clinical trials. Results: A total of 14 articles were obtained at the end of the selection. Of note, 13 articles had a statistically significant outcome (p≤0.005) for quality of life, cognitive, and emotional functions after intervention with art therapy, being the most used interventions, such as drawing, paintings, and sculptures. Conclusions: The results show significant impacts after the application of art therapy in its visual modality. However, studies with greater methodological rigor are needed to strengthen the evidence presented.